Permainan 3d Tentang Makanan 4 Sehat 5 Sempurna Untuk Anak - Pungki Dwi Setia Hadi (Melek IT : Information Technology Journal, 2019)
In the concept of 4 healthy 5 perfect, healthy food is food that contains 4 sources of nutrition that is staple food, side dishes, vegetables, fruits, and perfected with milk.kind knowledge of healthy foods by children resulted in them indiscriminate snack Which affects the deterioration of their health so that interfere with their learning activities in school. Therefore the authors are interested in making educational games as a medium of learning for children using 3D animation so that children can play while learning to know and understand about the perfect 4 healthy food 5.